4-Methylumbelliferone Treatment and Hyaluronan Inhibition as a Therapeutic Strategy in Inflammation, Autoimmunity, and Cancer - Nagy, Nadine; Kuipers, Hedwich F.; Frymoyer, Adam R.; Ishak, Heather D.; Bollyky, Jennifer B.; Wight, Thomas N.; Bollyky, Paul L. (Frontiers in Immunology, 2015)
Hyaluronan (HA) is a prominent component of the extracellular matrix (ECM) at many sites of chronic inflammation, including type 1 diabetes (T1D), multiple sclerosis (MS), and numerous malignancies. Recent publications have demonstrated that when HA synthesis is inhibited using 4-methylumbelliferone (4-MU) beneficial effects are observed in several animal models of these diseases. Notably, 4-MU is an already approved drug in Europe and Asia called “hymecromone” where it is used to treat biliary spasm. However, there is uncertainty regarding how 4-MU treatment provides benefit in these animal models and the potential long-term consequences of HA inhibition. Here, we review what is known about how HA contributes to immune dysregulation and tumor progression. Then, we review what is known about 4-MU and hymecromone in terms of mechanism of action, pharmacokinetics, and safety. Finally, we review recent studies detailing the use of 4-MU to treat animal models of cancer and autoimmunity.